2014
DOI: 10.1177/1756287214526767
|View full text |Cite
|
Sign up to set email alerts
|

Management of iatrogenic ureteral injury

Abstract: Iatrogenic injury to the ureter is a potentially devastating complication of modern surgery. The ureters are most often injured in gynecologic, colorectal, and vascular pelvic surgery. There is also potential for considerable ureteral injury during endoscopic procedures for ureteric pathology such as tumor or lithiasis. While maneuvers such as perioperative stenting have been touted as a means to avoid ureteral injury, these techniques have not been adopted universally, and the available literature does not ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
172
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(183 citation statements)
references
References 34 publications
4
172
0
7
Order By: Relevance
“…[8][9][10] The current study found distal ureter was the commonest site affected, suture ligation is the commonest injury and unilateral injuries were commoner, similar to study by Chalya et al in Tanzania.…”
Section: Discussionsupporting
confidence: 83%
“…[8][9][10] The current study found distal ureter was the commonest site affected, suture ligation is the commonest injury and unilateral injuries were commoner, similar to study by Chalya et al in Tanzania.…”
Section: Discussionsupporting
confidence: 83%
“…during caesarean section, the left lateral wall of the bladder as well as the left ureter are found closer to the midline [22]. More frequent occurrences of left ureteral lesions have been reported in the studies of this complication following gynecological and obstetric operations, mainly after hysterectomy with adnexa [17]. Complication of that type was also noted in the presented material.…”
Section: Discussionsupporting
confidence: 54%
“…The repair operation consists in removing the ligature/ureteral clip. In case of doubt as to the blood supply on the ligated site, the ischemic fragment of the ureter should be resected and reconstructed in a manner dependent on the location of the injury [12,17]. Table 4: Provision of blood preparations in women with injuries to the urinary organs after deliveries and surgical operations.…”
Section: Resultsmentioning
confidence: 99%
“…The ureteric strictures can be caused by several factors like stones, infections, fibrosis, malignancy, radiotherapy or in most cases by iatrogenic surgical trauma occurred during gynecological, colorectal and vascular surgery or after endourological surgery [10][11][12]. The strictures, that are too long or not suitable for treatment with end to end anastomosis, Boari flap or Psoas hitch technique, may require an ileal ureter, autotransplantation or nephrectomy.…”
Section: Discussionmentioning
confidence: 99%